Interleukin-41: a novel serum marker for the diagnosis of alpha-fetoprotein-negative hepatocellular carcinoma - Li, Yazhao; Wang, Haoyu; Ren, Danfeng; Li, Jingyu; Mu, Zihan; Li, Chaoyi; He, Yongchao; Zhang, Jiayi; Fan, Rui; Yin, Jiayuan; Su, Jiaojiao; He, Yinli; et al. (Frontiers in Oncology, 2024)
Background: For the lack of effective serum markers for hepatocellular carcinoma(HCC) diagnosis, it is difficult to detect liver cancer and identify its recurrence early. Methods: Databases were used to analyze the genes potentially associated with alpha-fetoprotein(AFP) . ELISA assay was used to detect the serum IL-41 in HCC, liver metastases, hepatitis, and healthy people. Immunohistochemical staining was used to analyze the relative quantification of IL-41 in HCC and paracancer tissues. Various survival curves were plotted according to clinical pathological data and helped us draw the ROC curve of IL-41 diagnosis of HCC. Results: The serum expression of IL-41 was highest in AFP negative HCC patients and significantly higher than that in AFP positive HCC and metastatic cancer patients. There was a significant negative correlation between elevated serum IL-41 and AFP(<1500ng/ml). The clinicopathological features suggested that the serum IL-41 level was significantly correlated with capsule invasion, low differentiation and AFP. High serum expression of IL-41 suggests poorer survival and earlier recurrence after resection, and IL-41 upregulated in patients with early recurrence and death. The expression of IL-41 was higher in HCC tissues of patients with multiple tumors or microvascular invasion. The ROC curve showed that serum IL-41 had a sensitivity of 90.17 for HCC and a sensitivity of 96.63 for AFP-negative HCC, while the specificity was higher than 61%. Conclusion: IL-41 in serum and tissue suggests poor prognosis and postoperative recurrence in HCC patients and could be a new serum diagnostic marker for AFP negative patients.